ANALISIS DIGITAL MARKETING ANTARA APLIKASI MYBCA DAN WONDR BY BNI - Chanda Vedalla Putra; Julia Ananda Caesaria; Jonathan Jonathan; Lia Willson; Mellysa Mellysa; Michelle Tan; Noval Christanto; Zendi Sia (CV. Denasya Smart Publisher, 2024)
This study analyzes the digital marketing strategies between two leading digital banking applications in Indonesia, namely MyBCA from Bank Central Asia (BCA) and Wondr by BNI from Bank Negara Indonesia (BNI). The research focuses on comparing features, digital marketing strategies, as well as customer acquisition and retention of the two applications. Data was obtained through secondary sources and analyzed qualitatively and quantitatively. The results show that although both applications have excellent features, MyBCA emphasizes simplicity and ease of use for general users, while Wondr by BNI focuses more on the younger generation with innovative and deeper personalization features. The digital marketing strategies employed by the two banks also differ, with MyBCA relying more on social media and email marketing, while Wondr by BNI predominantly uses influencer marketing. The conclusion of this study is that both applications have their respective strengths in meeting the needs of their customers.